2015
DOI: 10.1177/1687814015573787
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of bond-slip performance of corroded reinforced concrete under cyclic loading

Abstract: Reinforced concrete structures exposed to marine environment often sustain high levels of chloride-induced reinforcement corrosion, which causes reinforcement corrosion and resulting in degraded performance under cyclic service loading. This article studied the dynamic bond performance between corroded reinforcing and concrete under force controlled loading. Tests were carried out to evaluate the cyclic bond-slip degradation with different reinforcement corrosion levels. A series of 30 specimens with various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Independently of the bond element chosen, a bond law must be associated to characterize the behavior in the interface between concrete and reinforcement. In recent years, numerous research have been devoted to the study of bond models able to enclosure the bond-slip phenomenon under different load situations, as cyclic, thermal and confining loads [20]- [24], as well as different materials, e.g., fiber reinforced concrete [25], [26] and fiber reinforced polymer rebars [27], [28]. The introduction of such new bond models could be easily implemented into the system due to its high level of generalization with few changes in the graphical interface.…”
Section: Bond Modelsmentioning
confidence: 99%
“…Independently of the bond element chosen, a bond law must be associated to characterize the behavior in the interface between concrete and reinforcement. In recent years, numerous research have been devoted to the study of bond models able to enclosure the bond-slip phenomenon under different load situations, as cyclic, thermal and confining loads [20]- [24], as well as different materials, e.g., fiber reinforced concrete [25], [26] and fiber reinforced polymer rebars [27], [28]. The introduction of such new bond models could be easily implemented into the system due to its high level of generalization with few changes in the graphical interface.…”
Section: Bond Modelsmentioning
confidence: 99%
“…Previous research has demonstrated that this critical value is closely related to the concrete cover depth (Li et al, 2018), strength and type of concrete (Alavi-Fard and Marzouk, 2002; Campione et al, 2005; Hota and Naaman, 1997), and hoop confinement (Eligehausen et al, 1983) etc. Moreover, the deterioration of the bond strength is also related to the geometry and diameter of the steel bars (Li et al, 2007; Murcia-Delso et al, 2013; Zuo and Darwin, 2000), lateral pressure on the concrete (Li et al, 2018, 2022), level of corrosion (Kivell et al, 2015; Wang et al, 2019; Zhou et al, 2015) and environmental conditions (Hu et al, 2019; Xu et al, 2017). During the service life of the reinforced concrete structures, the steel bars may experience cyclic reversed loading with arbitrary amplitude (Zhang et al, 2021), and the hysteretic bond-slip relationship under reversed loading with variable amplitude shall be revealed to establish the bond stress-slip model.…”
Section: Introductionmentioning
confidence: 99%
“…Although it must be noted that there are obvious differences between electrochemical accelerated corrosion and natural corrosion in terms of electrochemical mechanism, corrosion products and corrosion morphology (Song et al, 2008), electrochemical accelerated corrosion can qualitatively characterize the degradation of structural performance. With the development of durability research, electrochemical technology has been applied to the study of mechanical properties of corroded steel bars, bond-slip performance of corroded reinforced concrete (Zhou et al, 2015;Zhou et al, 2017), structural performance degradation of reinforced concrete beams (Ou and Nguyen 2016) and piers (Yuan et al, 2018;Zhou et al, 2020). At present, many specifications are based on the data of electric accelerated corrosion method for the deformation calculation, mechanical performance evaluation and life prediction theory of corroded reinforced concrete members.…”
Section: Introductionmentioning
confidence: 99%